2021
DOI: 10.3892/mmr.2021.12183
|View full text |Cite
|
Sign up to set email alerts
|

Perampanel, an AMPAR antagonist, alleviates experimental intracerebral hemorrhage‑induced brain injury via necroptosis and neuroinflammation

Abstract: Spontaneous intracerebral hemorrhage (ICH) is a subtype of stroke with high mortality and morbidity due to the lack of effective therapies. The alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor antagonist perampanel has been reported to alleviate early brain injury following subarachnoid hemorrhage and traumatic brain injury by reducing reactive oxygen species, apoptosis, autophagy, and necroptosis. Necroptosis is a caspase-independent programmed cell death mechanism that serves a vital role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…However, they had no impact on cell viability at medium concentrations and were cytotoxic at higher concentrations (more than 50 µM) and more prolonged treatments (more than 24 h), particularly for perampanel. Although not as efficient as edaravone, metformin and perampanel also can increase cell viability, which is in line with data from previous studies [ 30 , 31 ]. Although these effects of perampanel were particularly obvious when using the MTT assay, which we have demonstrated to be more precise and sensitive to small changes in both cell lines, they were similar to those obtained with the other viability assays used in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, they had no impact on cell viability at medium concentrations and were cytotoxic at higher concentrations (more than 50 µM) and more prolonged treatments (more than 24 h), particularly for perampanel. Although not as efficient as edaravone, metformin and perampanel also can increase cell viability, which is in line with data from previous studies [ 30 , 31 ]. Although these effects of perampanel were particularly obvious when using the MTT assay, which we have demonstrated to be more precise and sensitive to small changes in both cell lines, they were similar to those obtained with the other viability assays used in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Whereas in higher concentrations, it decreases cell viability and increases ROS production. Thus, it seems that when in low doses, perampanel may protect neuronal cells from hypoxia and OGD, potentially due to its capability of reducing neuronal overexcitation [ 13 ], necroptosis, and neuroinflammatory events [ 30 ]. However, it seems that to be efficient, perampanel needs to be administered in low concentrations and simultaneously with hypoxic events.…”
Section: Discussionmentioning
confidence: 99%
“…A series of agents aimed at ameliorating necroptosis have improved neurological results in ICH ( Shen et al, 2017 ; Yang et al, 2021 ). Necrosulfonamide (NSA) is a specific inhibitor of MLKL.…”
Section: Introductionmentioning
confidence: 99%
“…The present study also demonstrated that UTI can alleviate brain edema, improve neurological function, relieve neuroinflammation response, and decrease hippocampal neuronal damage and necroptosis. Yang 49 reported that necroptosis and neuroinflammation were important mechanisms to lead EBI after ICH, and inhibition of these mechanisms can improve neurological outcomes, and reduce neuronal damage. Pan 50 also indicated that antinecroptosis chemical necrostatin-1 can suppress apoptosis and autophagy in mice ICH model.…”
Section: Discussionmentioning
confidence: 99%